Analysis of remaining motion using one innovative upper airway opening cervical collar and two traditional cervical collars - Jung, Matthias; Ehrlich-Treuenstätt, Gregor V. R. von; Keil, Holger; Grützner, Paul Alfred; Schneider, Niko; Kreinest, Michael (Scientific reports, 2021)
The aim of this study was to compare the remaining motion of an immobilized cervical spine using an innovative cervical collar as well as two traditional cervical collars. The study was performed on eight fresh human cadavers. The cervical spine was immobilized with one innovative (Lubo Airway Collar) and two traditional cervical collars (Stifneck and Perfit ACE). The flexion and lateral bending of the cervical spine were measured using a wireless motion tracker (Xsens). With the Weinman Lubo Airway Collar attached, the mean remaining flexion was 20.0 +/- 9.0 degrees. The mean remaining flexion was lowest with the Laerdal Stifneck (13.1 +/- 6.6 degrees) or Ambu Perfit ACE (10.8 +/- 5.8 degrees) applied. Compared to that of the innovative Weinmann Lubo Airway Collar, the remaining cervical spine flexion was significantly decreased with the Ambu Perfit ACE. There was no significant difference in lateral bending between the three examined collars. The most effective immobilization of the cervical spine was achieved when traditional cervical collars were implemented. However, all tested cervical collars showed remaining motion of the cervical spine. Thus, alternative immobilization techniques should be considered.